'Here to stay': changes to prescribing medication in general practice during the COVID-19 pandemic in New Zealand - Ben Hudson; Harrison Beadel; Umaya Ranaweera; Ruth Savage; Les Toop; Andrew Adiguna Halim; Anthony Dowell; Olivia Currie; Susan Bidwell; Zoe Windner; Geraldine Wilson (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONThe delivery of health care by primary care general practices rapidly changed in response to the coronavirus disease 2019 (COVID-19) pandemic in early 2020. AIMThis study explores the experience of a large group of New Zealand general practice health-care professionals with changes to prescribing medication during the COVID-19 pandemic. METHODSWe qualitatively analysed a subtheme on prescribing medication from the General Practice Pandemic Experience New Zealand (GPPENZ) study, where general practice team members nationwide were invited to participate in five surveys over 16 weeks from 8 May 2020. RESULTSOverall, 78 (48%) of 164 participants enrolled in the study completed all surveys. Five themes were identified: changes to prescribing medicines; benefits of electronic prescription; technical challenges; clinical and medication supply challenges; and opportunities for the future. There was a rapid adoption of electronic prescribing as an adjunct to use of telehealth, minimising in-person consultations and paper prescription handling. Many found electronic prescribing an efficient and streamlined processes, whereas others had technical barriers and transmission to pharmacies was unreliable with sometimes incompatible systems. There was initially increased demand for repeat medications, and at the same time, concern that vulnerable patients did not have usual access to medication. The benefits of innovation at a time of crisis were recognised and respondents were optimistic that e-prescribing technical challenges could be resolved. DISCUSSIONImproving e-prescribing technology between prescribers and dispensers, initiatives to maintain access to medication, particularly for vulnerable populations, and permanent regulatory changes will help patients continue to access their medications through future pandemic disruption.